Peningkatan Keterampilan Berbicara Mahasiswa melalui Praktik Berpidato dan Praktik Bercerita Menggunakan Video Pembelajaran Praktik Berbicara - Agus Joko Purwadi; Didi Yulistio; Rio Kurniawan (LP4MK STKIP PGRI Lubuklinggau, 2021)
The purpose of this study was to describe the improvement of speaking skills through speech practice and speaking practice using online learning videos for students of the Indonesian Language Education Study Program, Faculty of Teacher Training and Education, Bengkulu University. This research uses the Hopkins CAR procedure which is taken in two cycles. Each cycle is carried out through four stages, including the planning stage, the action stage, the observation stage, and the reflection stage. The data sources for this research were 40 students of S1 Indonesian Language Education in the even semester of 2020-2021. The research data is in the form of performances in the practice of making speeches and telling stories in learning practice videos. Collecting data using speaking test techniques by way of practicing speeches and storytelling and observation techniques to observe student activities in the online learning process. Data analysis used the mean formula and qualitative final results. The results showed that there was an increase in students' speaking skills which was carried out by practicing speeches and practicing storytelling through the use of online learning videos. This is evidenced by the process and learning outcomes in the first cycle with an average score of 75.6 in the good category, increasing in the second cycle with a score of 85.8 in the very good category. This improvement in speaking skills was followed by an increase in student activity in the learning process in the first cycle with an active attitude category with an average of 4.28 increasing in the second cycle to being very active with an average of 4.72, in discipline, responsibility, working together (collaborating), independence, and honesty are all categorized as very active.